ANALISIS PEMAHAMAN LITERASI KEUANGAN SYARIAH PADA PRODUK PEMBIAYAAN MURABAHAH (Studi Kasus Nasabah Pembiayaan Mikro Pada BPRS Haji Miskin Kc Payakumbuh) - Murdani, Riski; Mulyana, Cahya Agung (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Knowledge of Islamic financial products and services, or Islamic financial literacy, can influence a person's attitude in making economic decisions that are in line with Islamic sharia. In Islamic finance, the following rules apply: faith in God, abstaining from usury and other haram practices, avoiding gharar (uncertainty), and maysir (gambling/speculation). The customer's disagreement with the bank during the execution of the contract was identified as a problem in the author's initial observation. The main objective of this study is to fill the knowledge gap in Islamic financial literacy experienced by microfinance customers by identifying their experience in carrying out the practice, the challenges they face, and the opportunities that exist. Although this research is qualitative descriptive, this research includes field research. Primary and secondary sources of information were used to compile the results of this study. Observation, interviews, and documentation are the main methods of data collection in this study. Several microfinance customers, including Mrs. Mulyani, Mr. Nas, and Mrs. Lina, and Mrs. Dini Eka Putri, SE, the person in charge of BPRS Haji Miskin KC Payakumbuh branch, were interviewed. The understanding of financing clients is based on the findings of this study, micro increases in following Islamic financial literacy, increasing customer insights, customers can distinguish Islamic finance from conventional finance. The obstacles and risks faced by microfinance customers of BPRS Haji Miksin KC Payakumbuh in Islamic financial literacy are that most microfinance customers cannot take part in the Islamic finance education program because the distance to the customer's home and the location of the Islamic finance education is so far, because the program is only carried out at the head office.